2018
DOI: 10.1039/c8ra07003b
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric and flexible poly(styrene-b-ethylene/butylene-b-styrene)-zinc porphyrin–graphene hybrid composite: synthesis, performance, and mechanism

Abstract: Stretchable and flexible photoelectric materials are highly desirable for the development of artificial intelligence products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Owing to its soft nature and excellent aging resistance, SEBS has been widely used and can be easily accessible. [ 47 ] Figure 1c presented the stress–strain curve of SEBS ( M n = 153 kg mol −1 ) primarily used in this research. The fracture strain is as high as ≈1050% and two orders of magnitude higher than that of neat PM6, indicating that SEBS exhibits a remarkable ductility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its soft nature and excellent aging resistance, SEBS has been widely used and can be easily accessible. [ 47 ] Figure 1c presented the stress–strain curve of SEBS ( M n = 153 kg mol −1 ) primarily used in this research. The fracture strain is as high as ≈1050% and two orders of magnitude higher than that of neat PM6, indicating that SEBS exhibits a remarkable ductility.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its soft nature and excellent aging resistance, SEBS has been widely used and can be easily accessible. [47] Figure 1c The fracture strain is as high as ≈1050% and two orders of magnitude higher than that of neat PM6, indicating that SEBS exhibits a remarkable ductility. The elastic modulus of SEBS is determined to be 1.3 MPa, which is two to three orders of magnitude lower than those of common conjugated polymers.…”
Section: Mechanical Properties Of Ternary Blend Filmsmentioning
confidence: 96%
“…[ 4 ] One of the promising strategies to reinforce the mechanical robustness of PSCs is incorporating elastomers (i.e., poly(dimethylsiloxane) (PDMS) and styrene–ethylene–butylene–styrene (SEBS)) into the P D :SMA blend films. [ 5 ] These elastomers can increase the stretchability of the blend films due to their higher stretchability (>100–200%) compared to rigid conjugated materials. For example, Chen et al demonstrated that the addition of poly(dimethylsiloxane‐ co ‐methyl phenethylsiloxane) elastomer in all‐polymer blends effectively increased the stretchability of blend films.…”
Section: Introductionmentioning
confidence: 99%